1979
DOI: 10.1017/s0022112079000252
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on convective layer formation and merging in a differentially heated slot

Abstract: This work describes experiments in which a stably stratified salt solution is subjected to steady lateral temperature gradients. The criteria for the onset of layered convection are observed to agree with previously published stability analysis. Convective layers formed in this way are found to be statically unstable; they always merge two into one to form a new system. This process continues until the density jump at the solute interface between layers is larger than the density deficit produced by the side w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
1
6
1
Order By: Relevance
“…The recent study of Tanny & Tsinober (1988) categorized merging as 'first' and 'subsequent ' merging and proposed a Rayleigh-number criterion for the first merging to occur. In contrast to the observations of Wirtz & Reddy (1979), they concluded that the subsequent merging did not lead to a doubling of layer thickness.…”
Section: Introductioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The recent study of Tanny & Tsinober (1988) categorized merging as 'first' and 'subsequent ' merging and proposed a Rayleigh-number criterion for the first merging to occur. In contrast to the observations of Wirtz & Reddy (1979), they concluded that the subsequent merging did not lead to a doubling of layer thickness.…”
Section: Introductioncontrasting
confidence: 77%
“…Merging of the unstable adjacent layers to form a stable layered system has been previously observed by Wirtz & Reddy (1979) in narrow-slot experiments. Turner & Chen (1974) also qualitatively described merging of layers in a sugar-salt system.…”
Section: Introductionsupporting
confidence: 56%
“…Layer thickness is therefore a quantity that cannot be discussed independently of the history of the system. The process has not been studied very extensively (but see Wirtz & Reddy 1979, McDougall 1981, Young & Rosner 2000, Ross & Lavery 2009, and the coffee table experiment in ZS13). The layer thickness increases by a process of merging of neighboring layers.…”
Section: Evolution Of the Layer Thicknessmentioning
confidence: 99%
“…Hart (1973) considered merging of layers in the narrow-slot case and observed that it occurred owing to the breakdown of interfaces 'in a shower of turbulence and salt fingers'. Wirtz & Reddy (1979) studied in more detail the merging of layers in the narrow-slot configuration and as a result concluded that the merging process takes place by successive doubling of the layers thickness.…”
Section: Introductionmentioning
confidence: 99%